UPAYA MENINGKATKAN HASIL BELAJAR SISWA KELAS III PADA MATA PELAJARAN PENDIDIKAN PANCASILA DENGAN MATERI NILAI – NILAI PANCASILA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF NHT BERBANTUAN MEDIA PEMBELAJARAN PAPAN NILAI PANCASILA DI SDN JIWAN 02 MADIUN - Mariska Nida Farida; Anastasia Christina Damayanti; Jela Septiani; Melik Budiarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to improve Pancasila Education learning outcomes through theuse of Pancasila values board media with the Numbered Head Together (NHT)cooperative learning model for third-grade students at SDN Jiwan 02 Madiun. Thestudy used a Classroom Action Research (CAR) design based on the Kemmis andMcTaggart model, implemented in two cycles. The research subjects were 10third-grade students consisting of 4 male and 6 female students. Data werecollected through observation of student activities during learning, learningachievement tests in the form of pretest and posttest, and interviews with studentsto determine their responses to the media and learning model applied. Dataanalysis was conducted descriptively and quantitatively by calculating classaverages and learning completion percentages. The results showed verysignificant improvement from pre-cycle conditions to cycle II. The average learningoutcomes increased dramatically from 59 (pre-cycle) to 77 (cycle I) and reached96 (cycle II). The percentage of learning completion also increased from 20% (pre-cycle) to 70% (cycle I) and reached 100% (cycle II). Interview results showed thatstudents felt more enthusiastic and found it easier to understand Pancasila valuesthrough the colorful and interactive Pancasila values board media. This researchproves that the use of Pancasila values board media with the NHT model is veryeffective in improving third-grade students' Pancasila Education learningoutcomes.